2020
DOI: 10.1152/ajplung.00162.2020
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal budesonide/surfactant attenuates hyperoxia-induced lung injury in preterm rabbits

Abstract: Recent clinical trials have shown improvements in neonatal outcomes after intratracheal administration of combination budesonide/surfactant (ITBS)in infants at risk of bronchopulmonary dysplasia. However, the effect of ITBSon lung function and alveolar structure is not known. We aimed to determine the effect of ITBSon lung function, parenchymal structure and inflammatory cytokine expression in a relevant preterm animal model for bronchopulmonary dysplasia. Premature neonatal rabbits were administered a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…30,31 Given the diverse etiology of PARDS, 5,7 several animal studies have investigated the efficacy of using a surfactant as a vehicle for intratracheal steroids in reducing ALI in animal models of surfactant-depleted lung diseases, 23,25 MAS, 26 hyperoxia 27 , and injurious mechanical ventilation. 28,29 Regardless of the type of insult to induce ALI, these studies reported that intratracheal instillation of steroid-surfactant combination can alleviate ALI 23,[25][26][27][28][29] and reduce lung inflammation. 23,[26][27][28] Our model is a type of ALI in surfactant-insufficiency lungs, particularly with lung inflammation induced by LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Given the diverse etiology of PARDS, 5,7 several animal studies have investigated the efficacy of using a surfactant as a vehicle for intratracheal steroids in reducing ALI in animal models of surfactant-depleted lung diseases, 23,25 MAS, 26 hyperoxia 27 , and injurious mechanical ventilation. 28,29 Regardless of the type of insult to induce ALI, these studies reported that intratracheal instillation of steroid-surfactant combination can alleviate ALI 23,[25][26][27][28][29] and reduce lung inflammation. 23,[26][27][28] Our model is a type of ALI in surfactant-insufficiency lungs, particularly with lung inflammation induced by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Regardless of the type of insult to induce ALI, these studies reported that intratracheal instillation of steroid-surfactant combination can alleviate ALI 23,[25][26][27][28][29] and reduce lung inflammation. 23,[26][27][28] Our model is a type of ALI in surfactant-insufficiency lungs, particularly with lung inflammation induced by LPS. Our results demonstrated for the first time that intratracheal steroid-surfactant therapy is promising in this particular setting.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 It has been reported that intratracheal administration of budesonide with PS on the day of birth limited hyperoxia-associated disruption of lung function and structure in preterm rabbits. 54 In an observational study of 2 premature infants diagnosed with ARDS and receiving ventilator-assisted ventilation, Burak Deliloglu et al found that intratracheal administration of budesonide with PS can effectively improve pulmonary ventilation function and oxygenation index. 27 In a case-control study, T. Brett Kothe et al found that compared with the use of PS alone, the intratracheal administration of budesonide with PS can shorten the duration of mechanical ventilation.…”
Section: The Advantages Of Budesonidementioning
confidence: 99%
“…Biophysical and chemical stability of surfactant/ budesonide has been evaluated in a number of experimental studies confirming pulmonary and systemic antiinflammatory effects of this strategy in adult rabbits [95], mechanically ventilated preterm lambs [96], and rats [97]. In preterm neonatal rabbits, the combined administration attenuated hyperoxia-induced lung injury [98]. Moreover, pulmonary distribution of 2 natural surfactant preparations was recently tested, and both were shown to be effective vehicles for budesonide delivery [99].…”
Section: Biophysical and Chemical Stabilitymentioning
confidence: 99%